Literary Minstrelsy, 1770-1830 - Simpson, E. author. aut Link
IX, 215 p.
Keywords: This book argues that Romantic-era writers used the figure of the minstrel to imagine authorship as a social, responsive enterprise unlike the solitary process portrayed by Romantic myths of the lone genius. Simpson highlights the centrality of the minstrel to many important literary developments from the Romantic era through to the 1840s.